2016
DOI: 10.1111/ggi.12778
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of incidental mild cognitive impairment and dementia in a population‐based study

Abstract: Incidental MCI and ACD had prevalences of 13.5% and 6.9%, respectively, in the population-based study. Participants with these conditions showed cognitive/affective decline and impairment on computerized touch-panel tests in relation to vascular risk factors and exercise/hobbies. Geriatr Gerontol Int 2017; 17: 722-729.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…Therefore, we considered this age group as pre-elderly and recruited them into the study. The present study revealed the prevalence of MCI to be 28.8% which is in contrast to the study on incidental MCI that had a prevalence of 13.5% (Hishikawa et al, 2017).…”
Section: Demographic Data Analysiscontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, we considered this age group as pre-elderly and recruited them into the study. The present study revealed the prevalence of MCI to be 28.8% which is in contrast to the study on incidental MCI that had a prevalence of 13.5% (Hishikawa et al, 2017).…”
Section: Demographic Data Analysiscontrasting
confidence: 99%
“…Participants in this study were relatively younger compared to a similar study (Hishikawa et al, 2017). Even though most studies on cognitive impairment are conducted in people aged 65 years or older, we recruited patients aged 55 years and above.…”
Section: Demographic Data Analysismentioning
confidence: 99%
“…For example, vascular dysfunction may be associated with progression of both amyloid and τ pathology (51). In patients already diagnosed with Alzheimer’s disease dementia and mild cognitive impairment, both cognitive and affective dysfunction were increased among those with insulin resistance (52,53), and treating vascular risk factors helped to slow cognitive decline (54). The strong association between type 2 diabetes and vascular contributions to dementia should be carefully considered when implementing treatment and prevention measures.…”
Section: Toward a Precision Medicine Model For Dementia: Type 2 Diabementioning
confidence: 99%